MARKETING MIX DAN CITRA PERUSAHAAN MEMPENGARUHI LOYALITAS PELANGGAN - Yuli Setiawati; Eko Prabowo (JURNAL LENTERA BISNIS, 2023)
Customer loyalty is one of the things that are of concern to the company. This research was to analyze the influence of the marketing mix (marketing mix) and corporate image and whether simultaneously it can affect customer loyalty at the IFRA exhibition. The research methodology uses a quantitative approach using statistical calculation models and sampling techniques for 100 respondents to IFRA exhibitors. Testing the instrument results of the questionnaire was carried out by first carrying out validity and reliability tests by taking into account the Cronbach alpha provisions of> 0.70 by paying attention to the test results of correlation and multiple linear regression. Data analysis was assisted by the SPSS application using descriptive statistical test methods and hypothesis testing. The research results showed that there was a positive and significant influence on the marketing mix and corporate image variables on customer loyalty at the IFRA exhibition with contributions of 0.082 and 0.285 and simultaneously 76.1%.Keywords: Corporate Image; Customer Loyalty; Marketing Mix